2017
DOI: 10.25258/ijpcr.v9i3.8319
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Anticholinesterase Toxicity, Oxidative Stress and Antioxidant Status in Carbamate and Organophosphorus PesticidesExposed Agricultural Workers

Abstract: Among the numerous pesticides, anticholinesterase compounds are widely used. Their toxicity induced by cholinesterase inhibition at the synapses and neuromuscular junctions, leading to neurological disorders. Inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) has been used as sensitive biomarkers for pesticides exposure. In the present study, AChE and BuChE levels were estimated in agricultural workers exposed to carbamate and organophosphorus pesticides with average 9.8±3.5 years rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
5
2
1
Order By: Relevance
“…The results of the study showed that the MDA outcomes of the working group were higher than the control group (6.51 (SB 1.95) vs 2.344 (SB 8.823) nmol/mL). 10 Unlike the studies mentioned above, the results of this study did not indicate any association between the level of serum MDA and NO in children living in areas of chronic pesticide exposure (p = 0.994).…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the study showed that the MDA outcomes of the working group were higher than the control group (6.51 (SB 1.95) vs 2.344 (SB 8.823) nmol/mL). 10 Unlike the studies mentioned above, the results of this study did not indicate any association between the level of serum MDA and NO in children living in areas of chronic pesticide exposure (p = 0.994).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, Kisby et al study in USA reported that Serum MDA levels were 4.9 times and 24 times higher in farm workers and applicators, respectively, than in controls [24], also Vidyasagar et al results were in line with our results [25]. Moreover, our results are in consistent with a recent Egyptian study of Noshy et al which was conducted in El Monofya governorate, and reported an increased MDA levels in farm workers and pesticides applicators than the controls [26]. Moreover, other studies support these result [7] [9] [14] [27].…”
Section: Subjects and Methods Study Design And Settingssupporting
confidence: 93%
“…The present study revealed that SOD was significantly lower among exposed group compared to non-exposed group, (p-value = 0.000) (table 1), this is in agreement with Vidyasagar et al who reported that RBC SOD was lower among exposed versus control group [25]. Other studies in India and Egypt showed the same reduction in the SOD activity in the exposed groups [19][20][21][22][23][24][25][26]. In contrast to these results, some studies found an elevation of SOD levels in exposed group like Simoniello et al [30].…”
Section: Subjects and Methods Study Design And Settingssupporting
confidence: 91%
See 2 more Smart Citations